M4 Association of descriptors of breathlessness with diagnosis, self-reported severity of breathlessness and self-reported distress due to breathlessness in patients with advanced chronic obstructive pulmonary disease or cancer. (12th November 2015) - Chowienczyk, S; Javadzadeh, S; Booth, S; Farquhar, M
Abstract : Introduction and objectives: Verbal descriptors are important in understanding patients' experience of breathlessness. The selection of breathlessness descriptors may depend on the severity of breathlessness. 1 Our objective was to examine the association between selection of the breathlessness descriptors devised by Simon et al . with diagnosis, self-reported severity of breathlessness and self-reported distress due to breathlessness. 2 Methods: We studied 132 patients grouped according to their diagnosis advanced COPD (n = 69) or advanced cancer (n = 63), self-reported severity of breathlessness: mild breathlessness (Numerical rating scale (NRS) ≤3, n = 53), moderate breathlessness (4≤NRS≥6, n = 59) or severe breathlessness (NRS ≥7, n = 20), and distress due to breathlessness: mild distress (NRS ≤3, n = 31), moderate distress (4≤NRS≥6, n = 44) or severe distress (NRS ≥7, n = 57). Patients selected three breathlessness descriptors. The relationship between descriptors selected and patient groups was evaluated by cluster analysis. Results: Cluster analysis identified six clusters of descriptors: 'breathing restrictions', 'enough air', 'out of breath', 'air hunger', 'effort' and 'chest tightness'. Different combinations of clusters were associated with each diagnostic group. The association of clusters with patient groups differed depending on their severity of breathlessness and their distress due to breathlessness. The 'air hunger' cluster was associated with patients with moderate or severe breathlessness, the 'chest tightness' cluster was associated with patients with mild breathlessness. The 'air hunger' cluster was associated with patients with severe distress due to breathlessness. Conclusions: The relationship between clusters and diagnosis is not robust enough to use the descriptors to identify the primary cause of breathlessness. Further work exploring how use of breathlessness descriptors reflects the severity of breathlessness and distress due to breathlessness could enable the descriptors to evaluate patient status and target interventions. References: 1 Von Leupoldt A, Balewski S, Petersen S, et al . Verbal descriptors of dyspnea in patients with COPD at different intensity levels of dyspnea. Chest 2007;132 :141–147 2 Simon PM, Schwartzstein RM, Weiss JW, et al . Distinguishable sensations of breathlessness induced in normal volunteers. Am Rev Respir Dis . 1989;140 :1021–1027